Timing of high-definition transcranial direct current stimulation to the nondominant primary motor cortex fails to modulate cortical hemodynamic activity and improve motor sequence learning - Minxia Jin; Xiaomeng Xu; Ziwei Zhang; Weili Xia; Xiaoyu Lou; Zhongfei Bai (Journal of NeuroEngineering and Rehabilitation)
Abstract Background The relative timing of transcranial direct current stimulation (tDCS) and motor practice holds potential importance in modulating cortical activity and facilitating behavioral performance. Method A single-blind, randomized, cross-over experiment was conducted. Twenty healthy participants engaged in a sequential finger-tapping task with their left hand. High-definition anodal tDCS (1 mA, 20 min) was administered over the right primary motor cortex (M1) either during (concurrent-tDCS) or before the motor practice (prior-tDCS). A sham tDCS condition was also employed. The three tDCS conditions were separated by one-week intervals. Cortical hemodynamic activity in the prefrontal cortex (PFC), supplementary motor area (SMA), and M1 measured by functional near-infrared spectroscopy, as well as motor performance assessed by number of correct sequences were examined before (T1), immediately after (T2), and 24 h after the practice (T3). The data was subjected to a two-way repeated measures analysis of variance. Results No significant interaction or main effect of condition were found on motor performance. Regarding cortical hemodynamic activity, none of the regions of interest or channels exhibited a significant interaction effect or main effect of condition. No significant correlation between cortical activity and motor performance was found. Conclusion Our results cannot support the timing effect of single-session anodal tDCS on facilitating brain activity or improving motor performance. These results contribute to the growing body of evidence challenging the efficacy of a single session of exogenous stimulation as an adjunct to motor practice for promoting motor acquisition. Further research should explore alternative tDCS parameters, multiple sessions and various age groups.